2021
DOI: 10.21203/rs.3.rs-278055/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Improved perioperative outcomes and reduced inflammatory stress response in malignant robotic-assisted colorectal resections: a retrospective cohort study of 298 patients

Abstract: Background Robotic-assisted surgery is increasingly implemented for the resection of colorectal cancer, although the scientific evidence for adopting this technique is still limited. This study's main objective was to compare short-term complications, oncological outcomes, and the inflammatory stress response after colorectal resection for cancer performed laparoscopic or robotic-assisted. Methods We conducted a retrospective cohort study comparing the robotic-assisted approach to laparoscopic surgery for el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…To our knowledge, no studies, including larger sample sizes, have examined the association between the surgical stress response and long-term survival induced by RAS or LAS. A retrospective cohort study including 298 patients undergoing RAS or LAS for colorectal cancer in a planned setting indicated that LAS was associated with a significantly increased CRP response in the early postoperative course (21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, no studies, including larger sample sizes, have examined the association between the surgical stress response and long-term survival induced by RAS or LAS. A retrospective cohort study including 298 patients undergoing RAS or LAS for colorectal cancer in a planned setting indicated that LAS was associated with a significantly increased CRP response in the early postoperative course (21).…”
Section: Discussionmentioning
confidence: 99%
“…A Cox proportional hazard regression model was used to verify any potential effect modification of the postoperative CRP response and long-term survival, stratified by a low postoperative CRP response ( < 80 mg/L) compared to the group with a high CRP response (≥ 80 mg/L) across postoperative day one to day three. The assumptions underlying this cut-off threshold stem from data obtained in an observational study comparing patients undergoing planned RAS versus LAS for colorectal cancer (21). Results of both the unadjusted and adjusted analyses following PS matching were presented, Fig 1 . A two-sided p-value < 0.05 was considered statistically significant.…”
Section: Statisticsmentioning
confidence: 99%